Combined experimental and numerical approach to study electro-mechanical resonant phenomena in GaN-on-Si heterostructures. (September 2018) - Pribahsnik, F.P.; Bernardoni, M.; Nelhiebel, M.; Mataln, M.; Lindemann, A.
Abstract: Due to the intrinsic piezoelectric nature of Gallium Nitride (GaN), devices manufactured with such technology are in principle prone to experience electro-mechanically induced resonance phenomena under operating conditions. In this paper, we present the thorough approach combining simulation and experiment to study the occurrence and implications of such electro-mechanical resonances. A simple GaN-on-Si capacitor test structure was fabricated and electrically excited in order to activate the mechanical eigenmodes of the assembly which are measured by a Laser-Doppler-Scanning-Vibrometer. A multiphysics Finite Element (FE) model of the tested structures was built in order to perform harmonic analysis and to quantitatively study the effects of damping on displacement, stress and strain. A mathematical comparison on different aspects between the model and measurements show good agreement. This successfully verifies the methodology to model the dynamic resonance behaviour of piezoelectric active chips.